Well logging handbook - Serra, Oberto (Éditions TECHNIP, 2008)
Following the success of the Drilling Data Handbook, the publisher has designed this book to cover well logging principles and its applications. This handbook starts with a summary on geology and petrophysics focusing mainly on its applications. The wide range of logging measurements and applications is covered through eleven sections, each of them organized into four chapters. A large proportion of figures and tables are available to facilitate the understanding of more complex subjects. An exhaustive bibliography is also available at the end of this book for readers willing to deepen their knowledge on any particular topic. Finally, a simple and easy access to the information is made possible thanks to a detailed subject index. All in all, this is a valuable, strongly-bound, user-friendly book with useful information for those involved in all aspects and applications of well-logging.